The Implementation of Autodesk Inventor E-Module in The Study of Manufacturing Engineering Drawings: (Case Study at State Vocational High School 2 Kebumen) - Yuta Noviantoro Pratama Yoga; Darmono; Rizal Justian Setiawan; Khakam Ma’ruf (Journal of Educational Learning and Innovation (ELIa), 2024)
This research is experimental. This research was conducted at SMK Negeri 2 Kebumen in the 2022/2023 academic year. The sample selection in this study was class XII TP 3 as much as 35 as the control class and class XII TP 4 as the experimental class with a total sample of 35. The experimental class was treated in the learning process using E-Module learning media, and the control class was given treatment in the learning process with conventional methods. The design used in this study was the Pretest and Post Test Control Group Design. The research instrument is in the form of learning outcomes. To test the hypothesis using the paired sample t-test. The analysis was conducted descriptively. The results of this study indicate that the effect of the E-Module on student learning achievement shows a significant increase compared to learning without the E-Module. the result of the sig value is less than (α) = 0.05, then H0 is rejected and Ha is accepted which shows that there is an effect of the E-Module on student achievement.